Budget impact analysis of CYP2C19-guided voriconazole prophylaxis in AML. (1st August 2015) - Mason, Neil T.; Bell, Gillian C.; Quilitz, Rod E.; Greene, John N.; McLeod, Howard L.
Abstract : Objectives: The objective of this study was to determine the economic impact of proactive, CYP2C19 genotype-guided voriconazole prophylaxis in AML. Methods: An Excel-based model was created to project the cost of treating a simulated cohort of severely neutropenic AML patients undergoing antifungal prophylaxis. The model compares (i) standard prophylactic dosing with voriconazole and (ii) CYP2C19 genotyping of all AML patients to guide voriconazole dosing and prescribing. Results: Based on the model, genotype-guided dosing of voriconazole conservatively spares 2.3 patients per year from invasive fungal infections. Implementing proactive genotyping of all AML patients in a simulated 100 patient cohort is expected to save a total of $41467 or $415 per patient. Conclusions: The model, based on the robust literature of clinical and economic data, predicts that proactive genotype-guided voriconazole prophylaxis is likely to yield modest cost savings while improving patient outcomes. The primary driver of savings is the avoidance of expensive antifungal treatment and extended hospital stays, costing $30 952 per patient, in patients succumbing to fungal infection.